2017
DOI: 10.1016/j.apergo.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between arch height and foot length: Implications for size grading

Abstract: No significant relationships between arch height and foot length were found. The predictive value of the relationship was found to be poor. This holds significant implications for the current method of proportionate scaling of footwear in terms of fit and function to the midfoot region for a normative population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…However, a recent study reported that no significant relationships between arch height and foot length exist. [ 43 ] Furthermore, various methods of measuring NH are available [ 44 47 ] : nonweight bearing, 50% weight bearing, and 100% weight bearing, which could be associated with the significant difference among the taping conditions only during sitting and jogging in this study.…”
Section: Discussionmentioning
confidence: 95%
“…However, a recent study reported that no significant relationships between arch height and foot length exist. [ 43 ] Furthermore, various methods of measuring NH are available [ 44 47 ] : nonweight bearing, 50% weight bearing, and 100% weight bearing, which could be associated with the significant difference among the taping conditions only during sitting and jogging in this study.…”
Section: Discussionmentioning
confidence: 95%
“…To avoid introducing unnecessary confounding factors into the analysis, we selected a sample of women from the same population using the same shoe size [16,18,19,21,22,40,41]. However, among the women in the sample, there was a 24 mm difference between the longest and the shortest footprint, indicating that not all subjects have the same shoe fit.…”
Section: Discussionmentioning
confidence: 99%
“…Shoe fit is a complex issue that is influenced by multiple factors. There are differences in the ratio between the length and width of the foot by age [14,15], sex [16] and ethnicity [17][18][19][20], and even within the same sex and ethnicity [21][22][23]. To these factors should be added that the foot is a mobile structure that changes shape during different phases of gait [24], with a flattening of the foot during the mid-stance and elongation of the front of the rearfoot after forefoot contact [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some studies have shown that no meaningful relationship exists between arch height and foot length [46][47][48]. Additionally, one study that categorized foot posture into normal, lowarched and high-arched feet using arch index derived from inked footprint reported no significant differences in foot length, stature, body weight and body mass index between the three categories [49].…”
Section: Body Weight Arch Height and Foot Dimensionsmentioning
confidence: 99%